Malaysia's international trade issues : An impressionistic - Tang, T.C. (Pelanduk Pubns Sdn Bhd, 2008)
An Impressionistic View is recommended reading for university students and professional researchers who want to understand the issues of international trade in Malaysia. It is an in-depth review on possible comprehension of the unique Malaysian situation. It aims to provide a direction for more research on the subjects such as economic integration, imbalances, J-curve phenomenon, balancing items of balance of payments accounts and intra-industry trade. The objective is to study these issues and point out the many pitfalls and loopholes that need to be filled in before the issue of Malaysian international trade can be fully understood.